Governance of food safety in China's pre-made dishes industry: legal reforms, policy strategies, and international perspectives - Tang, Shuchen; Yang, YuLong; Li, Zilong (Frontiers in Nutrition, 2025)
The rapid growth of the pre-made dishes (PMD) industry in China has created new opportunities for rural revitalization and food industry modernization. However, food safety concerns remain a critical challenge, manifested in the absence of a unified standard system, incomplete certification mechanisms, flaws in traceability, and weaknesses in regulatory enforcement. This study conducts an empirical investigation of China's central and local legal documents, complemented by case analysis of recent food safety incidents, to identify the systemic gaps in governance of PMDs. Drawing on macro-, meso-, and micro-level perspectives, we propose a governance framework that integrates compulsory and voluntary standards, multi-stakeholder participation, and digital traceability platforms. Comparative insights from the European Union and the United States further highlight how China's regulatory innovations may contribute to the global discourse on ready-to-eat food safety. The findings suggest that legal and regulatory reform, supported by technology-driven solutions, is essential for ensuring consumer trust and sustainable industry development.